Prevalence and determinants of dysmenorrhea: A cross-sectional study - D V B. Anusha; K Shridevi; P Manoj; A Goparaju (MRIMS Journal of Health Sciences, 2021)
Background: Dysmenorrhea is a medical condition of pain during menstruation. A variety of factors effect dysmenorrhea which include early menarche, younger age, diet, prolonged and aberrant menstrual flow, psychological disturbances, and pelvic infections; these interfere with dysmenorrhea symptoms. Genetic factors, exertion, and activity patterns affect prevalence and severity of dysmenorrhea. Various studies in India revealed that the prevalence of dysmenorrhea varies from 33 to 79.67. Objective: To study the prevalence, characteristics, and determinants of dysmenorrhea. Materials and Methods: Community-based cross-sectional study was carried out which included 165 women from urban field practice area who have attained menarche but not completed menopause aged 15-50 years. Data were collected using semi-structured questionnaire by direct interview. The data were analyzed by percentages, proportions. Chi-square test was used. Results: The prevalence of dysmenorrhea was 60%. The correlation between the age and the dysmenorrhea grades was statistically not significant while the correlation between the age at menarche and the dysmenorrhea grades was found to be statistically significant. Majority of the participants had less than two hours of pain (33.3%) and most of them experienced the pain in the abdomen region (36.4%) and majority, i.e. 46.5% had mild pain. The duration of menstruation and duration of menstrual cycles were comparable in two groups but the heavy flow was significantly more in dysmenorrhea group compared to the normal group (P < 0.05) Conclusion: The prevalence of dysmenorrhea was high and it was related with age at menarche. Heavy flow was significantly more in dysmenorrhea patients.